Study of Crude Palm Oil (CPO) Handling and Storage Process in Palm Oil Mills in an Effort to Improve CPO Quality and Reduce the Risk of Contaminants Formation - Anita Syafrianti; Zulkifli Lubis; Jenny Elisabeth (Journal of Food and Pharmaceutical Sciences, 2021)
Crude Palm Oil (CPO) is palm oil obtained from the extraction or compression process of oil palm fruit flesh and has not been purified. Palm oil is usually used for food, cosmetic industry, chemical industry, and animal feed industry. Increasingly open insight and increasing consumer awareness of the importance of food safety and quality assurance supported by technological developments and laboratory analysis methods, new types of contaminants in food products are also found. Currently, the Indonesian government is facing challenges regarding the issue of 3-monochloro-1,2-propanediol ester (3-MCPD Ester) and glycidyl ester (GE) in palm oil which can hamper Indonesia's palm oil trade in the future. The practice in the field affects the quality of CPO and the retrieval of low-quality CPO is mixed with high-quality CPO. And the length of time the process of pumping CPO from reclaimed tanks to VCT affects the quality of CPO. So this study aims to modify the pumping time and storage time of CPO from Reclaimed tanks to VCT by mixing samples from VCT (fresh CPO) and samples from Reclaimed tanks (lower quality CPO).